Knowledge Management Sebagai Anteceden Kinerja UMKM - V. Ratna Inggawati; Bruno Hami (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2017)
MSMEs is a form of business classified as small to medium, from the size of the worker, the total value of net assets, the level of sales and investment is not large. Most MSMEs are owned and managed by individuals, so the most common problem is not being able to maintain performance continuity. One reason is that the owners and managers of MSMEs do not understand the importance of Knowledge Management. Knowledge and expertise are only stored as the thought of its predecessors in the form of tacit knowledge. It should be realized in the form of explicit knowledge. If that does not happen, the performance of MSMEs will be decreased, because the business depends on the memory or habit that occurred. If one day the predecessor retires or dies, then the business falls and eventually goes bankrupt.